Numerical study on the mechanisms of the SERS of gold-coated pyramidal tip substrates. (11th May 2016) - Li, Rui; Wang, Qiao; Li, Hong; Liu, Kun; Pan, Shi; Zhan, Weishen; Chen, Maodu
Abstract: In this paper, the physical enhancement mechanisms of the surface-enhanced Raman scattering (SERS) of pyramidal tip substrates are studied theoretically. We structure the periodic square-based arrays of adjacent nanometer pyramidal gold-coated tips on silicon. In order to determine the contribution of plasmonic or diffraction effects on the SERS, three-dimensional (3D) numerical simulations are implemented by taking into account the substrate coated with a gold thin film or a perfect electrical conductor thin film. The tip distance, metal coating thickness and incident light polarization angle are also optimized to investigate whether the further SERS signal can be enhanced.